Model of Growth of the Region’s Economy Based on the Index of Economic Complexity - A. L. Chupin; V. N. Zasko; D. E. Morkovkin; O. I. Dontsova (Финансы: теория и практика, 2024)
An important target of the UN Sustainable Development Goals (SDGs) is the efficient use of the planet’s resources. In this study, the authors show a strong exponential relationship between the economic complexity index and the efficiency of resource use in a country. The economic complexity index is a characterization of the productive capacity of large economies. This index measures the level of knowledge accumulated by a society that enables production. Assessing the level of a country’s index also makes it possible to predict future trends in the region’s economy. The model of economic sophistication index proposed by the authors includes the service economy, retail trade and manufacturing. Thus, in the paper, the authors identify how the economic complexity index affects the product level by defining the product space for each country and identifying the main products that contribute to a high product complexity index and prospective scalability, indicating the potential to produce better products in the future. Policies focused on increasing economic complexity and investing in staple products appear to be a priority for achieving sustainable development.